Prospek Pemberian Jaminan Kehilangan Pekerjaan Guna Memberikan Perlindungan Hak Pekerja dalam Sistem Hukum Ketenagakerjaan - Chintiya Oktaviani Silitonga; Solechan Solechan; Muhamad Azhar (Administrative Law and Governance Journal, 2022)
Abstract: Job loss insurance (JKP) is an additional post-employment social security program the issuance of the Job Creation Act is given specifically to workers who have termination of employment. This program is not fully running, because there is a minimum requirement for the contribution period and participant activity before to apply for benefits. This research aims to find out and understand the prospect of providing JKP in protecting workers who have termination of employment and the readliness of the organizer in implementing JKP. The research method used in writing this law is empirical juridical descriptive. The results of this study indicate the prospect of providing JKP has not been able to fully protect workers have been terminated. The existence of checking the participation of the social security program as a membership requirement will cause many workers not having the opportunity to take part in the program. Cash benefit is of low value and will not be enough for capital trying to be independent. Almost one year after the implementing regulations were issued, the organizers are not fully ready to implement a loss guarantee program work yet, it can be seen from the low level of understanding of workers about JKP, technical guideline that are not available yet, as well as systems and guidance human resources act as service implementers are still in the process. Keywords: Job Loss Insurance; Workers; Termination of Employment; Protection Abstrak: Jaminan kehilangan pekerjaan (JKP) merupakan program jaminan sosial tambahan pasca terbitnya UU Cipta Kerja yang diberikan secara khusus kepada pekerja yang mengalami PHK. Program ini belum sepenuhnya berjalan karena adanya ketentuan minimal masa iur dan keaktifan peserta sebelum dapat mengajukan manfaat. Penelitian bertujuan untuk mengetahui dan memahami prospek pemberian JKP dalam melindungi pekerja yang mengalami PHK dan kesiapan badan penyelenggara dalam menyelenggarakan program JKP. Penelitian ini menggunakan metode yuridis empiris bersifat deskriptif. Hasil penelitian menunjukkan, prospek pemberian JKP belum sepenuhnya dapat melindungi pekerja yang mengalami PHK. Pengecekan kepesertaan program jaminan sosial sebagai persyaratan kepesertaan akan mengakibatkan banyak pekerja tidak berkesempatan atas program, manfaat uang tunai bernilai rendah dan tidak akan cukup untuk modal berusaha mandiri. Hampir satu tahun pasca peraturan pelaksanaan terbit, badan penyelenggara belum sepenuhnya siap menyelenggarakan program JKP, terlihat dari rendahnya tingkat pemahaman pekerja terhadap JKP, petunjuk teknis belum tersedia, serta sistem dan bimbingan SDM masih dalam proses. Kata Kunci: Jaminan Kehilangan Pekerjaan; Pemutusan Hubungan Kerja; Perlindungan